Unhealthy Ultra-Processed Food, Diet Quality and Adherence to the Mediterranean Diet in Children and Adolescents: The DELICIOUS Project - Francesca Giampieri; Alice Rosi; Evelyn Frias-Toral; Osama Abdelkarim; Mohamed Aly; Achraf Ammar; Raynier Zambrano-Villacres; Juancho Pons; Laura Vázquez-Araújo; Nunzia Decembrino; Alessandro Scuderi; Alice Leonardi; et al. (Foods)
Background: Western dietary patterns worldwide are increasingly dominated by energy-dense, nutrient-deficient industrial foods, often identified as ultra-processed foods (UPFs). Such products may have detrimental health implications, particularly if nutritionally inadequate. This study aimed to examine the intake of unhealthy UPFs among children and adolescents from five Mediterranean countries (Italy, Spain, Portugal, Egypt, and Lebanon) involved in the DELICIOUS project and to assess the association with dietary quality indicators. Methods: A survey was conducted with a sample of 2011 parents of children and adolescents aged 6 to 17 years to evaluate their dietary habits. Diet quality was assessed using the Youth Healthy Eating Index (Y-HEI), the KIDMED index to determine adherence to the Mediterranean diet, and compliance with national dietary guidelines. Results: Increased UPF consumption was not inherently associated with healthy or unhealthy specific food groups, although children and adolescents who consumed UPF daily were less likely to exhibit high overall diet quality and adherence to the Mediterranean diet. In all five countries, greater UPF intake was associated with poorer compliance with dietary recommendations concerning fats, sweets, meat, and legumes. Conclusions: Increased UPF consumption among Mediterranean children and adolescents is associated with an unhealthy dietary pattern, possibly marked by a high intake of fats, sweets, and meat, and a low consumption of legumes.